Comparison Analysis of A Red Brick Wall With M-Cast Wall, Assessed from The Strength of Press, Time and Cost - Catur Prayogo; Novika Candra Fertilia (Journal of World Conference (JWC), 2021)
Currently there are several technologies and materials in the construction sector as substitutes for conventional building wall materials, including M-Cast and red brick. This study aims to determine the comparison of compressive strength, time and unit cost of wall work using M-Cast material and red brick based on conventional methods and SNI. Productivity data in this study were obtained by directly observing the speed of work in the field. The method used in this research is the Daily Record Sheet method and the SNI method. The job coefficient to calculate the work unit price analysis is obtained by calculating yourself based on the productivity value obtained.The results of the productivity analysis show that M-Cast has twice the strength compared to red brick, it can be seen from the final results of the compressive strength test at the age of the sample to 28 days where the red brick only has a strength of 53.92 - 58.50 Kg / cm² while M- Cast has a strength of 118.06 - 127.18 kg / cm², and the productivity value of M-Cast wall work in each type of observation is that the installation time required is 3 hours to install 1 piece of M-Cast with an area of ??-12m² where the time is 1 hour of installation and 2 hours of finishing Meanwhile, the red brick wall work time is 36 hours, where the installation time is 12 hours, plaster is 12 hours and finishing is 12 hours. The unit cost of the M-Cast wall works per 12m² is Rp. 7,690,000, and the red brick wall is Rp. 4,434,000.